Gonadotropin Regulated Testicular RNA Helicase, Two Decades of Studies on Its Structure Function and Regulation From Its Discovery Opens a Window for Development of a Non-hormonal Oral Male Contraceptive - Dufau, Maria L.; Kavarthapu, Raghuveer (Frontiers in Endocrinology, 2019)
Gonadotropin Regulated Testicular Helicase (GRTH/DDX25) is member of the DEAD-box family of RNA helicases present in Leydig and germ cells. GRTH is the only family member regulated by hormones, luteinizing hormone, through androgen action. Male mice with knock-out of the GRTH gene are sterile, lack sperm with arrest at round spermatids. GRTH participates on the nuclear export and transport of specific mRNAs, the structural integrity of Chromatoid Bodies of round spermatids, where mRNAs are processed and stored, and in their transit to polyribosomes, where it may regulate translation of relevant genes. GRTH has a central role in the control of germ cell apoptosis and acts as negative regulator of miRNAs which regulate protein expression of genes involved in the progress of spermatogenesis. In Leydig cells, GRTH gene transcription is regulated by LH via autocrine actions of androgen/androgen- receptor and has regulatory effects in steroidogenesis. In germ cells, androgen actions are indirect via receptors in Sertoli cells. Transgenic mice carrying GRTH 5’ flanking region-GFP permitted to discern regions in the gene which directs its expression upstream, in germ cells and downstream in Leydig cells, and the androgen-regulated transcription at interstitial (autocrine) and germ cell (paracrine) compartments. Further evidence for paracrine actions of androgen/androgen receptor is their transcriptional induction of Germ Cell Nuclear Factor as requisite up-regulator of GRTH gene transcription in round spermatids, linking androgen action to two relevant germ cell genes essential for the progress of spermatogenesis. A missense mutation of R to H at amino acid 242 of GRTH found in 5.8% of a patient population with azoospermia causes loss of the cytoplasmic phospho-GRTH species with preservation of the non-phospho form in transfected cells. Mice with knock-in of the human mutation, lack sperm due to arrest at round spermatids. This model permits to discern the function of phospho-GRTH. The GRTH phospho-site resides at a Threonine structurally adjacent to the mutant site found in patients. Molecular modelling of this site elucidated the amino acids that form the GRTH/PKA interphase and provide the basis for drug design for use as male contraceptive.